Universe 2.0: Black holes? No. Black stars! - Böhm-Mäder, Johannes (Frontiers in Physics, 2025)
Strong analytical evidence reveals that every solution of the Schwarzschild-Kerr metric, when continuously solving the metric across the event horizon, violates the conditions of the symmetry group, inevitably, which renders the long-term vision of black holes untenable. General relativity does not support a passable horizon hosting an infinitely concentrated mass in vacuum. The hitherto notion of black holes breaks down altogether. A new Schwarzschild solution, integrated within a massive shell, and a revaluation of the gravitational collapse yield a new vision of black stars of fluid, formed by a continuous progression of stacked horizons from the center to the surface. Thus, the current theory fundamentally differs from attempts to avoid horizons, such as mimickers, gravastars, boson stars, or gravitational metamaterials. The exterior view of Schwarzschild-Kerr black holes is not affected at all, but the inner view is obsolete. The information paradox and the conflict with the Pauli exclusion principle are solved and the Newtonian shell theorem is fully applicable in the relativistic context.